Analisis Psikologi Tokoh Utama Dalam Novel Catatan Juang Karya Fiersa Besari - Yamin, Nur; Maria E. D. Lering; Muhammad Lautama (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study aims to Describe and explain how the value of character education is contained in the novel catatan juang by fierza besari. The date source for this study was the novel catatan juang by fierza besari which was published mediakita of Jakarta 2017. The research technique used document review and literature study. The method used in this research technique used was document review and literature approach The results of this study suggest that the value of character education that is more ofthen found in the novel catatan juang by fierza besari is the value of character education contained in the novel catatan juang by fierza besari 10 out of 14 (cut) psikologi tokoh utama dalam novel catatan juang karya fierza besari diantaranya ego, dan super ego.